Comoros Tourism Sector Review : Discovering the Tourism Potential of Natural Wonders - World Bank (Washington, DC, 2014)
The Union of Comoros has struggled through political unrest for over thirty years. As a result, its tourism sector is still in the exploration phase of its life cycle. There have been initiatives by both the public and private sectors in the tourism industry, but to date, a lack of commitment from both sectors and external circumstances have prevented further growth. Comoros needs a tourism development plan that will provide a framework for all tourism stakeholders to the next phase of development. Strong institutional leadership from both the public and private sectors is one of the most important requirements to be addressed in order to support tourism in Comoros. The objective of this review is to conduct an analysis of the tourism sector performance and policies in the Union of Comoros. It presents policy options and recommendations at a country and sub-regional level. This review has been constructed as part of a larger Indian ocean regional tourism integration study including similar reports on the tourism sectors of Seychelles, Mauritius, and Madagascar. Combined recommendations provide a basis for practical approaches towards improved tourism competitiveness through leveraging regional integration opportunities across these economies. This report is structured as follows: section one gives introduction to the Comoros study; section two gives overview of the Union of Comoros tourism sector; section three presents key issues; section four gives recommendations; and section five gives conclusion.